The dynamic componential model of creativity: a theoretical framework for fostering creative teaching in higher education - Han, Weijing; Abd Rahim, Nur Aira; Zakaria, Noor Syamilah; Ghazali, Norliza (Human Resources Management Academic Research Society (HRMARS), 2023)
The rapid development of society has led to an increasing demand for teachers’ creative teaching in higher education institutions (HEIs) an imperative. However, teachers face significant challenges in implementing creative teaching practices. This paper aimed to explore the support system for fostering teachers’ creative teaching, by considering it as a dynamic process and analyzing the necessary preparations from the perspective of the creative process. By drawing upon the Dynamic Componential Model of Creativity (DCMC), this study explored the potential preparations for teachers’ creative teaching from the organizational dimensions. This study provided a macro-level analytical perspective for teachers’ creative teaching, offering valuable insights into championing teachers’ creativity and managing creativity within organizations.